Synthetic biology and opportunities within agricultural crops - Demi Sargent; Warren C. Conaty; David T. Tissue; Robert E. Sharwood (Journal of Sustainable Agriculture and Environment, 2022)
Abstract Conventional breeding techniques have been integral to the development of many agronomically important traits in numerous crops. The adoption of modern biotechnology approaches further advanced and refined trait development and introduction beyond the scope possible through conventional breeding. However, crop yields continue to be challenged by abiotic and biotic factors that require the development of traits that are more genetically complex than can be addressed through conventional breeding or traditional genetic engineering. Therefore, more advanced trait development approaches are required to maintain and improve yields and production efficiency, especially as climate change accelerates the incidence of biotic and abiotic challenges to food and fibre crops. Synthetic biology (SynBio) encompasses approaches that design and construct new biological elements (e.g., enzymes, genetic circuits, cells) or redesign existing biological systems to build new and improved functions. SynBio ‘upgrades’ the potential of genetic engineering, which involves the transfer of single genes from one organism to another. This technology can enable the introduction of multiple genes in a single transgenic event, either derived from a foreign organism or synthetically generated. It can also enable the assembly of novel genomes from the ground up from a set of standardised genetic parts, which can then be transferred into the target cell or organism. New opportunities to advance breeding applications through exploiting SynBio technology include the introduction of new genes of known function, artificially creating genetic variation, topical applications of small RNAs as pesticides and potentially speeding up the production of new cultivars with elite traits. This review will draw upon case studies to demonstrate the potential application of SynBio to improve crop productivity and resistance to various challenges. Here, we outline specific solutions to challenges including fungal diseases, insect pests, heat and drought stress and nutrient acquisition in a range of important crops using the SynBio toolkit.